Effect of rising water table in an unsaturated slope - Schnellmann, Reto (2011)
Recently, climatic changes have caused more extreme weather conditions such as heavy rain falls and droughts. Therefore, climatic changes are expected to produce increased variations in infiltration characteristics and positions of water table in slopes.